O direito à não autoincriminação na interpretação das cortes europeia e interamericana de direitos humanos - Nascimento, Vanessa Urquiola do (2015)
This research was developed through the Program of Graduate Studies at the Catholic University of Rio Grande do Sul, in the Masters in Criminal Sciences in the area Penal System and violence and in the search line on Legal and Criminal Contemporary systems. The work has the objective to identify the core of the Privilege against self-incrimination in criminal proceedings. The investigation is in the balance between the right to proof and the right of the accused has not to produce evidence against himself, in order to respect the dignity of the human person, without, however, any evidential activity is frustrated. In this context, it appears that the proposed issue involves a complexity of variables that influence the conclusions drawn on the job, such as: a) the need to comply with consolidated legal or jurisprudential procedures; b) the necessity or not of collaboration of the accused in the evidence; c) interference or not the suspect's body for obtaining of the evidence assembled; and d) the degree of body intervention to be supported by the accused. Therefore, considering that the privilege against self-incrimination has the status of human right, it sought through, especially the analysis of the trial of the European and Inter-American Courts of Human Rights, to elucidate the intricacies of this problem, expose the various solutions found and discuss them in the light of respect for the essence of the human person, weaving up, before this explanation, brief notes about the jurisprudence of national constitutional courts of Brazil and the United States, with a view in the first case, the reality of what part of this study, and in the second case, the peculiar position of the US Supreme Court restriction of that right.